Conceptual design of dual purpose coconut dehusking machine - Mohd Fauzi Mohd Yunus; Sharifah Nurulhuda Tuan Mohd Yasin; Nur Kamila Syahirah Md Fadzli; Siti Nor Balqis Suhaimi; Nur Hamizah Zainuddin (Southeast Asian Journal of Technology and Science, 2020)
Coconut dehusking is one of the procedures that take numbers of time and efforts. Mostly they involve human labour with the help of manual tools that made from steel or wood crowbar. However, most of them, only focus to dehusk only the coconut. Therefore, the objective of this paper is to determine the conceptual designs of dual operating dehusking machine. This paper discusses similar methods and compares the final design of other dehusking machine. There were three conceptual designs been analysed in term of design matrix and discussed in details this paper. The result showed that third design is chosen as a final design due more practicality and lower cost to be fabricated. It can be concluded that the selected final design meets the requirement of the criteria that have been stated.